Enhancing English Proficiency at Ngubalan Elementary School in Tulungagung: An Integrated Approach - Muh Ibnu Sholeh; Muhammed Ramadhan Abd Allah Mohamed; Himad Ali; Sokip Sokip; Asrop Syafi’i (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study aims to evaluate the effectiveness of an integrated approach in enhancing English proficiency at Ngubalan Elementary School in Tulungagung. This research employs a qualitative approach, focusing on interviews as the primary instrument. Interviews were conducted with English teachers, students in grades 4-6, the principal, and parents. The interview data were analyzed using interactive analysis techniques consisting of Data Reduction, Data Presentation, and Conclusion Drawing. The findings indicate that the integrated approach successfully increased student motivation and engagement in learning English through the use of diverse media and methods. Teachers and the principal observed improvements in students' English skills, while parents noted positive changes in their children's English abilities at home. Challenges included limited facilities and time, but measures such as teacher training and collaboration with external parties have been taken to address these obstacles.